Proceedings of a roundtable event 'Is communicating the concept of nutrient density important?'. Issue 1 (16th February 2020) - Lockyer, S.; Cade, J.; Darmon, N.; Flynn, M.; Gatenby, S.; Govindji, A.; Quick, B.; Raats, M.; Rayner, M.; Sokolović, M.; Spiro, A.; Sritharan, N.; et al.
Abstract: The British Nutrition Foundation held a 1‐day roundtable event to gather views from a wide range of stakeholders on the relevance and importance of the concept of nutrient density in supporting and motivating people to make healthier dietary choices. The opportunities and barriers associated with the use of this concept were also explored. The roundtable involved experts from research, public health nutrition, dietetics, retail and nutrition science communication, and this report describes the main themes emerging from the discussions. High obesity prevalence rates indicate that, on average, we are consuming too many calories relative to energy requirements; yet, the quality of our diets, with respect to certain vitamins and minerals and fibre, seems to be falling somewhat short of recommendations. Addressing this issue may require a more holistic approach than the current focus on restricting single nutrients prevalent in public health messaging internationally. Most members of the roundtable felt that communicating the concept of nutrient density may help in encouraging healthier food choices and dietary patterns that are higher in nutritional quality. However, while nutrient profiling has been used to guide front‐of‐pack labelling and in restricting the advertising of less healthy foods to children, there is a lack of consensus on the precise definition of a 'nutrient dense' food or which nutrients should be used as markers of the 'healthiness' of foods/drinks, and the term seems to be poorly understood by consumers and health professionals alike. Therefore, further work is required if tools around this concept are to be developed to try and successfully promote behaviour change.